IMPROVEMENT OF SYSTEM FOR MANAGING CONFLICT OF INTERESTS IN CIVIL SERVICE AS NECESSARY FACTOR FOR CURBING CORRUPTION - Oleshko O.M. (Pressing Problems of Public Administration, 2017)
The phenomenon of con ict of interests as a source of corruption in public authorities is considered; a number of measures have been proposed to improve the system for managing con ict of interests in the civil service.